Everyday cognition and some problems of cognitive socialization - Dozhdikova, Raisa N. (Journal of the Belarusian State University. Sociology, 2019)
The author has attempted to apply V. S. Stepin’s methodological principles of classifying the notion of «everyday cognition» to the analysis of the contemporary state of cognitive socialization. The programming impact of everyday cognition on the character of perceiving scientific and pseudo-scientific knowledge on the basis of using statistical data obtained from the students’ questionnaires is analyzed. Certain problems of contemporary school education, as well as propaganda of science and criticism of pseudo-science are explicated. The author comes to the conclusion that everyday cognition can serve as a specific indicator cognitive socialization, the level of assimilating and fixing scientific achievements.